The Study of the Educational Program Competence Model Based on the Intellectual Analysis of the Labor Market Professional Requirements - D. V. Minaev (Управленческое консультирование)
The educational standards of higher education — FGOS3++ require designing educational programs (EP) based on professional competencies in demand in the labor market. It is rec ommended to use professional standards. This way has certain disadvantages. For example, professional standards describe labor functions, but in the EP competencies are required. The use of professional standards in the development of the EP obviously determines a certain lag in the reaction in the labor market changes. An alternative to such EP design is a direct analysis of market requirements. Intelligent Analysis (IA) tools: data mining and machine learning can facilitate such analysis. An overview of developments in this direction is given. The results of the application of IA based on the KNIME analytical platform for determining the competence model of the EP in the feld of project management are presented. Automation aﬀected:the collection of requirements for more than 6000 vacancies of employers of the Head Hunter online resource; the analysis of texts presented in natural language (descriptions of EP of diﬀerent universities, professional standards and guidance materials of professional associations — SOVNET-Agile, IPMA OCB&ICB). Based on these data sets was carried out: tokenization, collocation of terms and topics, clustering of topics, the cross-classifcation of professional standards and guidance materials based on a pre-trained competence model of the EP. The results confrmed the efciency of the used technique. Such analytics allows us to dynamically systematize descriptions of professional activities and formulate considerations about the elements, structure, and mutual correspondence of the EP competence models and the competencies natural models on the labor market. In combination with the traditional expert assessment, it can contribute to the formation of a more complete isomorphism between the qualifcations of EP and professional activity.